Intersexual Person: Problems and the Right in Physical Sex - Mahanarongchai, Sumalee (Thammasat Journal, 2025)
This research article studies the meaning, types, and problematic cases of intersexual persons. The study shows that intersexual persons are different from other types of gender-diverse persons due to the lack of the right to determine their original sex. Being born ambiguous in their genitals, they have their bodies treated as disorders of sex development. Their gender is first determined, and their physical sex, though unclear but changeable at puberty, is then quickly and surgically altered to match the predetermined gender. So, the physical sex given to intersexual persons is not their natural and original sex, but is based on binary sex (either male or female) influenced by culture. Determining gender and sex to intersexual persons in this way reflects outdated bioethics, which focuses only on culture in contrast to natural diversity. The results are thus enormous physical and mental sufferings of these persons, as they are stigmatized and normalized in and for culture from birth. Supporting the right for intersexual persons to determine their physical sex, not only their gender, reflects social recognition of their humanity under the new bioethics which focuses on the balance between nature and culture.